Hubungan Pengetahuan dan Keaktifan Lansia Dalam Melakukan Senam Lansia Dengan Kejadian Nyeri Sendi Pada Lansia di Desa Paribun Kecamatan Barusjahe Kabupaten Karo Tahun 2021 - Ernawati Br Barus (Pusat Riset dan Inovasi Nasional, 2021)
Elderly can be said to be the final stage of development in the human life cycle. Meanwhile, article 1 paragraph (1), (2), (3), (4) of Law no. 13 of 1998 concerning health states that an elderly person is someone who has reached the age of more than 60 years (Maryam, 2011). A decrease in muscle function and strength will result in a decrease in the ability to maintain postural balance or body balance in the elderly. Joint pain is an inflammation of the joints which is characterized by joint swelling, redness, heat, pain and movement pain. (Santoso, 2009). The type of data used is primary data taken directly from respondents using a questionnaire. The statistical test used is the chi-square test ∝= 0.481. The results of the analysis showed that the majority of elderly people with less experience experienced joint pain (43.5%). The results of the chi-square statistical test obtained p= 0.481, which means there is a relationship between knowledge and activeness of the elderly in doing elderly exercise with the incidence of joint pain in the elderly. Seeing the results of this research, the health workers on duty should provide education about exercise for the elderly and joint pain.